A Randomized Study of Passive versus Active PrEP Patient Navigation for a Heterogeneous Population at Risk for HIV in South Florida. (23rd May 2019) - Doblecki-Lewis, Susanne; Butts, Stefani; Botero, Valeria; Klose, Katherine; Cardenas, Gabriel; Feaster, Daniel
Effective approaches to promoting pre-exposure prophylaxis (PrEP) and linkage to PrEP care among those who may benefit the most from PrEP has proven to be a major challenge. We designed and pilot tested a strengths-based case management (SBCM) intervention for PrEP linkage. Adults interested in PrEP and meeting criteria (n = 61) were randomized to passive referral (control) or active SBCM (treatment). Outcomes measured were completion of provider visit, initiation of PrEP, and time to initiation of PrEP. Overall, 34% initiated PrEP by 12 weeks: 9 (29%) in the control group and 12 (40%) in the treatment group. The mean time to PrEP initiation was 13.1 weeks (95% confidence interval, 12.0-14.2) with no difference between groups ( P = .382). There was a 21% difference in achieving a provider visit between the treatment and control groups (53.3% versus 32.3%) by 12 weeks ( P = .096). Participants encountered financial, logistical, social, and provider-related barriers to PrEP access. Strengths-based case management–based patient navigation is a promising strategy for assisting PrEP seekers in obtaining a medical provider visit and initiating PrEP.